Pengetahuan dan Sikap tentang Bantuan Hidup Dasar (BHD) pada Guru Sekolah Menengah Atas di Sleman DIY - Muninggar, Anggis Yustika; Kusumawati, Happy Indah; Alim, Syahirul (Jurnal Keperawatan Klinis dan Komunitas (Clinical and Community Nursing Journal), 2024)
Background: Out-of-hospital cardiac arrest (OHCA) is the leading cause of death worldwide. OHCA can occur in any settings such as in school. Basic life support (BLS) is an intervention to get the greatest chance of OHCA survival outcomes. Teachers are expected to have a role to provide BLS at the scene of medical emergency. The success of BLS outcome is influenced by knowledge and attitudes toward BLS.Objective: To assess knowledge and attitude towards basic life support among senior high school teachers in Sleman DIY.Method: Cross sectional design was used in this descriptive study. This study was conducted from February-March 2022. A total of 103 senior high school teachers in Sleman were participated and selected using cluster random sampling, simple random sampling, and consecutive sampling. Data were collected using Public Knowledge and Attitude towards BLS questionnaire. Data were analyzed using univariat to analyze respondents characteristic, knowledge, and attitude towards BLS.Results: The result of the study showed that 64 respondents (62,1%) had good BLS knowledge, especially on the questionnaire item which mentioned the first thing to do when there is someone collapse. The highest responses were found toward two questionnaire items, i.e.: BLS training is important in every workplace (70,9%) and general community should receive BLS training (81,6%). Conclusion: Most of high school teachers in Sleman have good level of BLS knowledge. The attitude towards BLS is shown as that they are aware that BLS training is important for general community and in every workplace and they are willing to receive BLS training.INTISARILatar belakang: Out-of-hospital cardiac arrest (OHCA) menjadi penyebab utama kematian di seluruh dunia. Bantuan hidup dasar (BHD) merupakan tindakan yang dilakukan untuk meningkatkan kesempatan hidup pada korban henti jantung. Guru sebagai tenaga pendidik, diharapkan dapat memiliki peran dan keterampilan dalam penanganan kasus kegawatdaruratan. Keberhasilan tindakan BHD dipengaruhi oleh pengetahuan dan sikap tentang BHD.Tujuan: Mengetahui gambaran pengetahuan dan sikap tentang BHD pada guru SMA di Sleman, DIY.Metode: Penelitian ini merupakan penelitian deskriptif kuantitatif dengan rancangan cross sectional. Penelitian dilaksanakan pada bulan Februari-Maret 2022. Responden dalam penelitian ini berjumlah 103 orang yang terdiri dari guru Sekolah Menengah Atas di Kabupaten Sleman yang pengambilan sampelnya dengan teknik cluster sampling, simple random sampling, dan consecutive sampling. Pengambilan data dilakukan dengan kuesioner Public Knowledge and Attitude towards BLS. Analisis univariat digunakan untuk menganalisis data karakteristik responden, gambaran pengetahuan BHD, dan gambaran sikap terhadap BHD.Hasil: Hasil penelitian menunjukkan bahwa sebanyak 62,1% guru memiliki pengetahuan BHD yang baik, terutama pada pernyataan mengenai tindakan pertama yang harus dilakukan ketika melihat seseorang dalam keadaan tidak sadar. Sebagian besar responden memiliki sikap sadar bahwa pelatihan BHD penting dilakukan di segala jenis pekerjaan (70,9%) dan masyarakat umum berhak mendapatkan pelatihan BHD (81,6%). Simpulan: Sebagian besar guru SMA di Sleman memiliki pengetahuan BHD yang baik. Sebagian besar guru SMA menunjukkan sikap sadar akan pentingnya memiliki pengetahuan dan keterampilan BHD pada masyarakat umum di bidang pekerjaan apa pun, serta memiliki keinginan yang tinggi untuk mengikuti pelatihan BHD.